Тривалість зберігання та вихід товарної продукції плодів огірка за дії екзогенних антиоксидантів - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Оlesia; Данченко, Олена Олександрівна; Данченко, Елена Александровна; Danchenko, Olena (My University, 2011)
UK: Розглянуто вплив обробки антиоксидантним препаратом АКМ на тривалість зберігання та вихід товарної продукції плодів огірка. EN: The influence of AKM antioxidant treatment on the duration of storage and yield marketable products of cucumbers hybrids F1 Masha and Aphina at a storage temperature of 6 and 8 °C was investigated. Found that the use of exogenous antioxidants can increase the duration of cucumber fruit storage on 7 days, reduce the natural loss of weight by 67,8% and increase the yield of marketable products to 89,1 – 92,5%.
Effect of exogenous antioxidants on the duration of storage and yield marketable products of cucumber
Keywords: огірки; зберігання; антиоксиданти; товарна якість; природна втрата маси; температура зберігання; cucumber; storage; antioxidant; commercial quality; the natural decline in mass; storage temperature